Analisis Pengaruh Literasi Zakat dan Kepercayaan terhadap Minat Membayar Zakat Melalui Zakat Digital pada Masyarakat di Kabupaten Sidoarjo - Anggraini, Yuanita Nur; Indrarini, Rachma (Universitas Negeri Surabaya, 2022)
In the digital era, the collection of zakat funds can be done through a digital platform belonging to the amil zakat institution. However, with this convenience, there is a risk of data leakage that can affect the interest of the people of Sidoarjo Regency to pay their zakat through digital zakat. This study aims to determine the effect of literacy and zakat trust on interest in paying zakat through digital zakat in the people of Sidoarjo Regency. In this study using quantitative methods using a linkert scale measuring instrument. With multiple linear regression data analysis technique using the IBM SPSS 25 program. The results of this study indicate that zakat literacy partially does not affect the interest in paying zakat through digital zakat in the people of Sidoarjo Regency. Trust has an influence on the interest in paying zakat through digital zakat in the people of Sidoarjo Regency. And literacy and trust simultaneously affect the interest in paying zakat through digital zakat in the people of Sidoarjo Regency.